Multisystem Inflammatory Syndrome Complications after Infection COVID-19 in Children - Saetew, Paparsinee; Rueangsawat , Sarawut; Teepapal, Thanida (Journal of The Royal Thai Army Nurses, 2023)
Multisystem Inflammatory Syndrome in Children (MIS-C) is a severe complication following the novel Coronavirus Disease 2019 infection. It is a rare and potentially fatal condition. This review article aims to present a conceptual framework, principles and theories of Multisystem Inflammatory Syndrome in Children which were analyzed and synthesized from books, academic articles and related research. The following issues were presented: 1) The concept of Multisystem Inflammatory Syndrome in Children’s complications; 2) Guidelines for the treatment of Multisystem Inflammatory Syndrome in Children; 3) Guidelines for the prevention of Multisystem Inflammatory Syndrome in Children; and 4) The role of nurses in the care of children with Multisystem Inflammatory Syndrome in Children and provide the guidelines for taking care of children with Multisystem Inflammatory Syndrome in Children in order to prevent the development of severe symptoms.